Handbook of Green computing and blockchain technologies - Saini, Kavita 1976-; Khari, Manju (CRC Press, Taylor & Francis, 2022)
This handbook provides a computational perspective on Green Computing and Blockchain Technologies. It presents how to not only identify challenges using a practical approach but how to also develop strategies for addressing industry challenges. Handbook of Green Computing and Blockchain Technologies will have a practical-oriented approach, include solved examples, highlighting standardization, industry bodies, and initiatives. Case studies are included for a deeper understanding of Blockchain and are related to real-time scenarios. The book will analyze the current research and development in Green Computing and Blockchain analytics, study the existing related standards and technologies, and provide results on implementation, challenges, and issues in today’s society. Those that will benefit from this handbook include researchers, software developers, both undergraduate and postgraduate students in Industrial Systems, Manufacturing, Information Technology, Computer Science, Manufacturing, Communications, and Electrical Engineering
1. Green Computing and Blockchain Fundamentals 2. Green Computing and Internet of Things (IoT) 3. Coalescence of Neural Networks and Blockchain 4. Blockchain in Administration: Advances and Implications of Decentralized Applications for Sharing Information 5. Combination of Convolutional Neural Networks and Blockchain in Handwritten Digit Recognition 6. How Blockchain Technology Can Transfigure the Indian Agriculture Sector: A Review 7. The COVID-19 Outbreak: Blockchain-Secured Transactions in Supply Chain Orchestration 8. Blockchain Technology in the Energy Sector: A Systematic Review of Challenges and Opportunities 9. Blockchain and Government 10. Blockchain in Healthcare: A Smart and Hierarchical Decentralized Tracing Application in Healthcare by Blockchain 11. Blockchain for IoT Edge Devices and Data Security 12. Blockchain for Medicine and Healthcare
Keywords: Aufsatzsammlung